1991
DOI: 10.1002/jsfa.2740550312
|View full text |Cite
|
Sign up to set email alerts
|

Protein solubility and emulsifying capacity in frozen stored fish mince

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Other investigators have found that the extractable protein decreases with increased storage time in the frozen state. Thus, Srikar and Reddy (1991) in pink perch, LeBlanc and LeBlanc (1989) in cod, Owusu-Ansah and Hultin (1986) in red hake, De Koning et a1 (1985) in minced hake, Thomson and Mackie (1982) in cod, Laird et a1 (1981) in cod and haddock, Kelleher et a1 (1981) in red hake and Poulter and Lawrie (1977) in cod, whiting and lemon sole, have shown that the quantity of protein extracted from fish muscle decreases during the storage of different species at various temperatures. On the other hand, Crupkin et a1 (1982) hardly observed any change in the extractability of both total myofibrillar proteins and actomyosin in hake stored in ice for 11 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have found that the extractable protein decreases with increased storage time in the frozen state. Thus, Srikar and Reddy (1991) in pink perch, LeBlanc and LeBlanc (1989) in cod, Owusu-Ansah and Hultin (1986) in red hake, De Koning et a1 (1985) in minced hake, Thomson and Mackie (1982) in cod, Laird et a1 (1981) in cod and haddock, Kelleher et a1 (1981) in red hake and Poulter and Lawrie (1977) in cod, whiting and lemon sole, have shown that the quantity of protein extracted from fish muscle decreases during the storage of different species at various temperatures. On the other hand, Crupkin et a1 (1982) hardly observed any change in the extractability of both total myofibrillar proteins and actomyosin in hake stored in ice for 11 days.…”
Section: Resultsmentioning
confidence: 99%
“…These modifications can be attributed to denaturation and subsequent aggregation of the proteins of the myofibrillar fraction (Shenouda 1980). Srikar and Reddy (1991) suggested that it could also happen that the decrease in protein solubility was due or partially due to the low neutral lipid (eg triglyceride) content. A very low triglyceride content was found by Fernandez-Reiriz et a1 (1992a), who also showed that this fraction disappeared in the initial stages of frozen or ice storage (Fernandez-Reiriz et a1 1992a, b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…triglyceride) content. Neutral lipids have the capacity to dissolve free fatty acids and to neutralize their hydrophobicity, which exerts desolubilizing effect on the proteins (De Koning, Milkovitch, & Mol, 1985;Pastoriza & Samperdro, 1994;Srikar & Reddy, 1991). Free fatty acids and fatty oxides interacted with protein surface to form hydrophobic regions and decreased the extraction of proteins (Sikorski, Olley, & Kostuch, 1976).…”
Section: Extraction Of Proteinmentioning
confidence: 97%
“…Solubility is an important functional property of postmortem muscle protein (Asghar and others 1985;Li-Chan and others 1985). Salt-soluble proteins may influence the texture, moisture retention, emulsifying capacity, and tenderness of meats, and they can be utilized to evaluate the degree of protein denaturation (Hageman 1988;Srikar and Reddy 1991;van Laack and others 1993). The inclusion of antioxidants in surimi wash water has resulted in improved functionality of myofibrillar proteins from beef heart (Wang and Xiong 1998;Parkington and others 2000) and turkey white muscle (Decker and others 1993).…”
Section: W Ater Affects Food Stability By In-mentioning
confidence: 99%